The development of mobile robot for air pollution data capture (POPOBOT) - A. Rahman, Khairul Azlan (2011)
In the Modern era, the environmental issues have given significant impact to the human live. The air pollution indoor and outdoor environment sometimes dangerous to the human health and it needs to be justified. To fulfill this purpose, telemeasurement process and technique should be used. Therefore, in this research, the